2020
DOI: 10.1002/slct.202001401
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of Novel (E)‐Hydroxystyryl Aralkyl Sulfones as Neuroprotective Agents

Abstract: A novel class of (E)‐hydroxystyryl aralkyl sulfones were designed and synthesized as neuroprotective agents. Their neuroprotective properties were assessed by several antioxidant models including 1,1‐diphenyl‐2‐picrylhydrazyl (DPPH) free radicals scavenging model, neuronal protective effects against neurotoxins such as hydrogen peroxide (H2O2), 6‐hydroxydopamine (6‐OHDA) and 1‐methyl‐4‐phenylpyridinium iodide (MPP+). Besides, the anti‐inflammatory activity was evaluated by lipopolysaccharide (LPS)‐induced nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…This suggested that the formation of hydrogen bond may play a more significant role in PhO⋅ stabilization than p‐π conjugation. This observation was further supported by the lack of free radical scavenging activity in compounds with only a single hydroxyl group (including 6 c – d and another compound from the previous study [18b] ). Taking all results into consideration, it was suggested that intramolecular hydrogen bond was inevitable in free radical scavenging.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…This suggested that the formation of hydrogen bond may play a more significant role in PhO⋅ stabilization than p‐π conjugation. This observation was further supported by the lack of free radical scavenging activity in compounds with only a single hydroxyl group (including 6 c – d and another compound from the previous study [18b] ). Taking all results into consideration, it was suggested that intramolecular hydrogen bond was inevitable in free radical scavenging.…”
Section: Resultssupporting
confidence: 60%
“…The level of NO production reflects the degree of inflammation, and evaluating the inhibitory effect of NO production is a valuable strategy for measuring the anti‐inflammatory activities of target compounds. Lipopolysaccharide (LPS) has been reported to activate BV2 microglial cells to release NO, which can be used in the model of evaluating anti‐inflammatory effects [15d,18b] …”
Section: Resultsmentioning
confidence: 99%